A trajectory of social innovations for the direct purchase of organic food by food services: a case study in Florianópolis, Brazil - Pugas, Adevan da Silva; Rover, Oscar José; Martinelli, Suellen Secchi; Teodolino, Francele Contarini (Frontiers in Sustainable Food Systems, 2023)
Introduction Although interest in the so-called short food supply chains (SFSC) has grown in recent decade, studies and social innovations that emerged from this phenomenon have made little progress in involving food actors outside the home. The article analyzes the conditioning factors for forming short food supply chains involving food services and organic farmers’ organizations, understanding them as potential social innovations. Methods The research used questionnaires with food services, participant and non-participant observations, and secondary data analysis with regional farmers’ organizations in the Greater Florianópolis region. Results Food services, which mostly do not yet purchase organic products from local producers, are interested in integrating purchasing initiatives directly from farmers and their organizations. However, they have presented several conditions for this. Nevertheless, farmers have the capacity, at least in part, to respond to the required conditions due to their innovative trajectory and socio-organizational capacity. Discussion The provision of food services, associated with the trajectory of social innovations in SFSC by farmers around Florianópolis, shows a potential to converge different interests for the generation of new initiatives, following the innovative trajectory led by social actors who work with the rural area. This could increase the impact of ongoing SFSC initiatives, ensuring consumers access local food, even when eating out.